MYOCARDIAL REMODELING IN ISCHEMIC HEART DISEASE - A. N. Zakirova; R. G. Oganov; N. E. Zakirova; G. R. Klochkova; F. S. Musina (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study the myocardial remodeling features in patients with stable angina depending on disease severity and experienced myocardial infarction (MI).Material and methods. 148 male patients with stable angina were examined and randomized into 3 groups (G1-G3). 52 patients of G1 had angina of I-II functional class (FC). 49 patients of G2 had angina of III FC, and 47 patients of G3 had angina of IV FC. History of MI had 79,5, 87.2 and 92.6% of patients in G1, G2 and G3 respectively. 35 healthy men were included into control group. Coronarography, bicycle ergometry and 24-hour ECG monitoring was performed. Left ventricular (LV) function and remodeling was assessed with echocardiography.Results. G3 patients had LV eccentric hypertrophy as a result of postinfarction cardiosclerosis which accompanied with LV systolic dysfunction, a myocardial stress increasing and LV spherification. G1 patients had no any significant disorders of LV systolic function.Conclusion. Severe ischemic heart disease is associated with a dysadaptive remodeling unlike mild ischemic heart disease, which is associated with an adaptive myocardial remodeling.